Influence of composition on morphology of semiconducting oxides microwires. (November 2021) - Giovannelli, F.; Bah, M.; Delorme, F.; Monot-Laffez, I.
Abstract: In this study, a crystal growth route is described in order to obtain semiconducting oxides microwires with various morphologies. Ceramic rods of ZnO, SnO2, Zn2 SnO4 and In2 O3 are sintered at 900 °C during 10 h in air. Then the rod is subjected to crystal growth in an optical furnace. At high temperature, a vaporization-condensation mechanism takes place when heated and leads to the growth of microwires on the rod itself. In 20 min, the microwires can reach a size longer than 100 μm in the growth direction. The shape of the microwires depends on the material space group. A hexagonal shape is obtained in the case of ZnO, whereas a cubic-like shape appears in the case of In2 O3 . Moreover, it is shown that doping is possible with this process and does not proceed in sublimation-condensation but in a diffusion process. Capacitance variation measurements carried out on the Ni doped ZnO microwires using scanning capacitance microscopy evidenced a decrease of carrier concentrations along the microwire. This carrier profile is consistent with that induced by diffusion process in solid phase. The shape and the size of the microwires depend on the doping element. Doped ZnO, In2 O3 and SnO2 single microwires, with well faceted and specific shape, have been thus achieved by this technique. Highlights: It is a new rapid and original route to synthesize semiconducting oxides microwires. Doped ZnO, In2 O3 and SnO2 single crystalline microwires have been achieved in an optical furnace. The shape and size of the microwires depend of the doping element. Single microwire can be easily isolated and manipulated.